2014
DOI: 10.7150/ijbs.9241
|View full text |Cite
|
Sign up to set email alerts
|

Abnormality in Wnt Signaling is Causatively Associated with Oxidative Stress-Induced Intestinal Tumorigenesis in MUTYH-Null Mice

Abstract: MUTYH is a DNA glycosylase that excises adenine paired with 8-oxoguanine to prevent mutagenesis in mammals. Biallelic germline mutations of MUTYH have been found in patients predisposed to a recessive form of familial adenomatous polyposis (MAP: MUTYH-associated polyposis). We previously reported that Mutyh-deficient mice showed a high susceptibility to spontaneous and oxidative stress-induced intestinal adenoma/carcinoma. Here, we performed mutation analysis of the tumor-associated genes including Apc, Ctnnb1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…In most of these lesions, accumulation of βcatenin and cyclin D1 in the nuclei of atypical epithelial cells was observed. These features were consistent with the characteristics of the small intestinal tumors observed in experimental models of human hereditary colorectal cancer using Mutyh −/− or Msh2 −/− mice treated with KBrO 3 [8][9][10]. Thus, the neoplastic proliferative lesions observed in this study may have arisen from oxidative stress-related mechanisms.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In most of these lesions, accumulation of βcatenin and cyclin D1 in the nuclei of atypical epithelial cells was observed. These features were consistent with the characteristics of the small intestinal tumors observed in experimental models of human hereditary colorectal cancer using Mutyh −/− or Msh2 −/− mice treated with KBrO 3 [8][9][10]. Thus, the neoplastic proliferative lesions observed in this study may have arisen from oxidative stress-related mechanisms.…”
Section: Discussionsupporting
confidence: 89%
“…Because neither preneoplastic nor neoplastic lesions were observed at all doses of KBrO 3 in Nrf2 +/+ mice, it is likely that the lack of Nrf2 was involved in the development of oxidative stress-associated neoplastic proliferative lesions in the small intestine. However, the incidences and multiplicities of tumors in the small intestine have been reported to be dramatically increased in Mutyh −/− or Msh2 −/− mice treated with KBrO 3 for 16 weeks [8][9][10]. KBrO 3 is able to increase 8-OHdG in DNA at the carcinogenic target site [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that chronic oxidative stress experimentally induced by KBrO 3 resulted in multiple tumour formation in the small intestines of Mutyh-null mice (16,17). We also reported that mismatch repair-deficient mice show a susceptibility to KBrO 3 -induced intestinal carcinogenesis (18).…”
mentioning
confidence: 81%
“…First, we compared the antitumor effects of celecoxib and DM‐celecoxib on the human colon cancer cell lines HCT‐116 and DLD‐1, in which the Wnt/β‐catenin signaling pathway is constitutively active, and analyzed downstream mediators of the aforementioned pathway. Subsequently, we examined the effect of these compounds on intestinal cancer development in Mutyh ‐deficient ( Mutyh −/− ) mice, which lack the mammalian DNA glycosylase MutY homolog (MUTYH) and develop multiple intestinal cancers in the presence of oxidative stress (likely caused by over‐activation of the Wnt/β‐catenin signaling pathway) …”
mentioning
confidence: 99%